2018
DOI: 10.1080/15389588.2017.1410545
|View full text |Cite
|
Sign up to set email alerts
|

The effect of correct cross-chest clip use on injury outcomes in young children during motor vehicle crashes

Abstract: Correct cross-chest clip use appeared to reduce injury in crashes, and there was no evidence of serious clip-induced injury in children in 5-point harness restraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…A recent analysis of real world crash data from NASS-CDS between 2003 and 2014 (Woodford et al, 2018), reported that correctly used cross chest clips approximately halved the odds of moderate to serious injury among children aged 0-4 years, with the majority of this effect occurring in children under 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent analysis of real world crash data from NASS-CDS between 2003 and 2014 (Woodford et al, 2018), reported that correctly used cross chest clips approximately halved the odds of moderate to serious injury among children aged 0-4 years, with the majority of this effect occurring in children under 12 months of age.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the former could not be met by either of the tested chest clips. The absence of significant additional neck loads, taken together with the lack of observed serious neck injuries associated with chest clips reported in Woodford et al (2018), suggest that any potential risk associated with this is likely minimal, and should be balanced against the potential for benefit via better retention of the harness straps on childrens' shoulders. The latter is a commonly observed form of misuse (Brown et al, 2010a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation